Structural damage assessment of RC slab strengthened with POZD coated steel plate under contact explosion. (February 2023) - Wang, Wei; Wei, Guangshuai; Wang, Xing; Yang, Jianchao
Abstract: To reveal the anti-explosion capacity of polyisocyanate oxazodone (POZD)-coated steel RC composite structural slabs, a explosion test was carried out for 2 test models. Using ANSYS/LS-DYNA, the damage mode and maximum mid-span deflection of steel plate-RC plate and POZD coated steel plate-RC plate were explored, and the experimental results were compared. Parametric analysis of the charge, POZD, steel plate and concrete slab thickness on the anti-explosion performance of the POZD-steel plate-RC slab. The results show that increasing the thickness of POZD, steel plate and RC slab can effectively reduce the POZD-steel – RC slab mid-span deflection. The POZD coating and steel plates increased the tensile area of concrete and improved the flexural and load carrying ability of the concrete slabs.